2005
DOI: 10.1111/j.1365-2559.2005.02097.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of S100 proteins in normal human tissues and common cancers using tissue microarrays: S100A6, S100A8, S100A9 and S100A11 are all overexpressed in common cancers

Abstract: S100A6, S100A8, S100A9 and S100A11 are all expressed in common cancers, especially breast cancer. In addition, S100A11 undergoes a nucleocytoplasmic translocation which may have a direct influence on the proliferation of the cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
168
1
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(185 citation statements)
references
References 37 publications
12
168
1
4
Order By: Relevance
“…In an immunohistochemical survey of S100 protein expression in 28 tissue types and 21 tumor types, Cross et al found expression of S100A6 and S100A8 in 12% and 29% of breast cancers. 37 Our findings are consistent with those of Carlsson et al who found downregulation of S100A6 regardless of pathological stage and up-regulation of S100A8 in breast cancer using serial analysis of gene expression (SAGE). 38 Kennedy et al have shown that BRCA1 is capable of repressing several of the members of the S100A family including S100A8 and that functional BRCA1 is required for this repression.…”
Section: Protein Identificationsupporting
confidence: 93%
“…In an immunohistochemical survey of S100 protein expression in 28 tissue types and 21 tumor types, Cross et al found expression of S100A6 and S100A8 in 12% and 29% of breast cancers. 37 Our findings are consistent with those of Carlsson et al who found downregulation of S100A6 regardless of pathological stage and up-regulation of S100A8 in breast cancer using serial analysis of gene expression (SAGE). 38 Kennedy et al have shown that BRCA1 is capable of repressing several of the members of the S100A family including S100A8 and that functional BRCA1 is required for this repression.…”
Section: Protein Identificationsupporting
confidence: 93%
“…Although S100A6 overexpression in pancreatic and other cancers, including gastric (Yang et al, 2007), thyroid (Brown et al, 2006), breast (Cross et al, 2005) and colorectal (Komatsu et al, 2000) has been documented, its precise role in cancer is not known. In pancreatic cancer, the expression of S100A6 appears to correlate with aggressive disease in that high levels of tumour S100A6 are associated with poorer outcome (Vimalachandran et al, 2005), whereas pancreatic cancer cells depleted of S100A6 are less invasive (Ohuchida et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10] Subsequent studies showed that S100A6 may also be involved in the regulation of cancer progression. 11 The deregulation of S100A6 expression during malignant transformation has thus far been described in human pancreatic cancer, malignant thyroid neoplasms, malignant melanoma, breast cancer, hepatocellular carcinoma, lung cancer, prostate cancer, and colorectal carcinoma.…”
mentioning
confidence: 99%